2015
DOI: 10.1159/000438998
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Frequency Stimulation on Sensory Thresholds in Chronic Pain Patients

Abstract: tection and vibratory detection thresholds also significantly increased with HFS compared to ON states (p = 0.04 and p = 0.01, respectively). In addition, HFS significantly decreased 10-and 40-gram pinprick detection compared to OFF states (both p = 0.01). No significant differences between OFF, ON and HFS states were seen in thermal and thermal pain detection. Conclusion: HFS is a new means of modulating chronic pain. The mechanism by which HFS works seems to differ from that of traditional SCS, offering a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 18 publications
2
66
1
1
Order By: Relevance
“…These findings suggested that for back pain there were no observable differences between 1 and 10 kHz frequencies suggesting interesting clinical and basic science questions that will need to be explored and addressed. These findings are in line with previous observations by North et al [64] and Youn et al [66], suggesting that 10 kHz may not be the only effective frequency and is not indispensable to paresthesia-free SCS. It remains unclear what essential property of tonic paresthesia-free SCS governs the pain inhibition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings suggested that for back pain there were no observable differences between 1 and 10 kHz frequencies suggesting interesting clinical and basic science questions that will need to be explored and addressed. These findings are in line with previous observations by North et al [64] and Youn et al [66], suggesting that 10 kHz may not be the only effective frequency and is not indispensable to paresthesia-free SCS. It remains unclear what essential property of tonic paresthesia-free SCS governs the pain inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a study in 2012 by Perruchoud and colleagues revealed no significant difference between 5-kHz HF-SCS and sham stimulation in a cohort of individuals with stable chronic back pain who already were receiving traditional SCS [21]. Other data suggest significant improvement in pain sensory thresholds in chronic pain patients with frequencies as low as 1.15 kHz compared to traditional SCS [66]. Therefore, paresthesia-free SCS for pain inhibition may also be induced by SCS at a frequency that is lower than 10 kHz.…”
Section: Review Of Clinical Datamentioning
confidence: 99%
“…It has since long been known that large fibers mediate touch, proprioceptive and vibration sense, and that C‐fibers transmit pain and temperature stimuli . In a clinical study using quantitative sensory testing, the effect of 10 kHz SCS on sensory processing was evaluated, and it was confirmed that 10 kHz stimulation alters processing in large fibers without modulating C‐fibers . Indeed, 10 kHz stimulation resulted in a decreased vibratory sense and pinprick detection versus classical tonic stimulation (Aα and Aβ), but no effect on temperature thresholds (C‐fibers) was noted for 10 kHz versus tonic SCS, confirming the simulation data clinically.…”
Section: Opinionmentioning
confidence: 93%
“…There is but one study where SCS with slightly higher frequencies than conventionally used (200–1200 Hz) was applied in 20 patients who underwent QST (Quantative Sensory Testing) examination during traditional SCS as well as with the higher frequencies. The only significant outcomes discovered were elevated pressure detection and pressure pain thresholds with higher frequency SCS.…”
Section: High Frequency Scsmentioning
confidence: 99%